The role of the arterial glycocalyx in sphingosine-1- phosphate induced cardioprotection in the isolated heart of the Wistar rat - Araibi, Hala (Department of Human Biology, 2018)
Background: Ischemic heart diseases (IHD) are a leading cause of death among cardiovascular diseases. Unfortunately, the myocardial damage due to ischemia in IHD may be worsened by reperfusion therapy, a phenomenon called ischemic-reperfusion (I/R) injury. Coronary vascular damage is a key feature of I/R injury. Among the coronary vascular structures, the endothelial glycocalyx is a delicate polysaccharide and protein-rich layer that plays an important role in the regulation of vascular permeability, and is easily damaged during I/R. Sphingosine-1-phosphate (S1P) is a membrane phospholipid metabolite that has been shown to protect the heart against I/R. It has also been shown to regulate the synthesis of glycocalyx, but its effects on coronary endothelial glycocalyx damage and possible mechanism during I/R are unknown. Therefore, we hypothesized that S1P-induced cardioprotection is mediated by modulation of the glycocalyx during I/R in the isolated rat heart. Methods: Isolated male Wistar hearts were perfused on a Langendorff system with Krebs-Henseleit buffer via retrograde perfusion at constant temperature and pressure. The hearts were stabilized and pre-treated with S1P (10 nM for 7 minutes) before inducing 20 minutes of global ischemia, followed by 60 minutes reperfusion. Functional parameters were recorded throughout the protocol, including left ventricular developed pressure (LVDP), left ventricular end diastolic pressure (LVEDP), heart rate (HR) and coronary flow (CF). Ventricular infarct size was measured by using triphenyltetrazolium chloride stain. Coronary net filtration rate (NFR) was calculated as a ratio of the amount of transudate to CF. Cardiac edema was assessed by calculating the heart wet/dry weight ratio and histologically quantifying size of the interstitial compartment. The shedding of the glycocalyx was estimated by measuring the release of the glycocalyx component syndecan-1 in the coronary effluent using enzyme-linked immunosorbent assay (ELISA) and determining relative syndecan-1 staining intensity between groups in immuno-stained wax sections of perfusion-fixed hearts. In addition, the histo-morphology of the myocardium was assessed using hematoxylin and eosin staining. Results: The cardiac performance was depressed after I/R, as was reflected by decreased LVDP (P=0.02 vs. control), and an increased LVEDP (P<0.0001 vs. control). I/R also significantly increased infarct size (P=0.04 vs. control). Treatment with S1P before I/R significantly decreased infarct size (P=0.01 vs. I/R), but did not improve the post-ischemic decrease in LVDP or stabilize the LVEDP, and had no effect on CF. I/R significantly increased release of syndecan-1 in the coronary effluent (P=0.0002 vs. control). Immunohistochemically-stained imaging also revealed syndecan-1 staining intensity was significantly decreased or absent in ischemic hearts (P≤0.001 vs. control). Pretreatment with S1P had neither effect on syndecan-1 level in the coronary effluent nor on the intensity of syndecan-1 signal in immuno-stained sections (P=n.s vs. I/R). Histological analysis of cardiac edema revealed an increase in the extracellular area in ischemic hearts compared to the control hearts (P≤0.001 vs. control), and S1P treatment decreased the extracellular area (P≤0.01 I/R+S1P vs. I/R). The NFR, and heart wet/dry ratio were not significantly different post-reperfusion between the groups and S1P had no effect on these parameters. Conclusion: This study showed that pretreatment with S1P protects the heart against I/R injury, as was indicated by the decreased infarct size, and decreased extracellular cardiac edema. S1P had no effect on hemodynamic performance or the shedding of syndecan-1. These results suggest that S1P-induced cardioprotection is not mediated by protection of the glycocalyx via stabilization of syndecan-1. However, it is possible that S1P may stabilize other minor glycocalyx components which were not measured in this study, such as heparan sulphate and hyaluronic acid. This is the first study that evaluated syndecan-1 in the cardiac effluent of the isolated heart of rats with global ischemia, and the study opens up prospects for further investigation of the role of the glycocalyx in other models of I/R injury, such as the more clinically-relevant regional ischemia disease model.